2019
DOI: 10.1007/s13197-019-04147-0
|View full text |Cite
|
Sign up to set email alerts
|

Volatome finger printing of red wines made from grapes grown under tropical conditions of India using thermal-desorption gas chromatography–mass spectrometry (TD–GC/MS)

Abstract: The current study evaluated the key characters of aroma composition in diversified red wines (Cinsaut, Grenache, Cabernet Franc, Petit Verdot, Cabernet Sauvignon, Nielluccio, Tempranillo, Syrah, Merlot and Caladoc). Out of hundreds of volatile compounds 64 compounds were considered for study. Different groups consisting of fatty acids, volatile alcohols, aldehydes, esters, volatile phenols and terpenes were analysed using gas chromatography mass spectrometry coupled with thermal desorption (TD-GC-MS). Among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
9
2
Order By: Relevance
“…Ionene, as one of the aromatic components of green tea and red wines [ 29 ], has been identified as a thermal degradation product of β-carotene [ 30 ]. Because of its unique structural characteristics, ionene used to be an important application material for various industrial applications [ 31 ] and for efficient organic solar cells [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ionene, as one of the aromatic components of green tea and red wines [ 29 ], has been identified as a thermal degradation product of β-carotene [ 30 ]. Because of its unique structural characteristics, ionene used to be an important application material for various industrial applications [ 31 ] and for efficient organic solar cells [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, peak 3 was tentatively identified as neochlorogenic acid [ 42 ]. Peak 4 had UV λmax at 245 and 310 nm, m / z [M − H] − 337.0941, and was tentatively determined as coumaroylquinic acid [ 29 ]. Peak 5 had UV λmax at 285 nm, which was similar to marein, molecular ions at m / z [M − H] − 449.1105, and was automatically matched to C 21 H 22 O 11 [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoterpenes provide basic floral aroma, and C 6 alcohols rose-like scent, higher alcohols and ethyl esters of C 4 ÷ C 10 fatty acids contribute to the fruity scents, while the occurrence of norisoprenoids is connected with some specific ageing aroma and abundance of fatty acids that can contribute to a -goaty‖ flavor of wine [25]. Somkuwar et al [23] evaluated aroma composition by analyzing 64 compounds in various red wines (Cinsaut, Grenache, Cabernet Franc, Petit Verdot, Cabernet Sauvignon, Nielluccio, Tempranillo, Syrah, Merlot and Caladoc) made from grapes grown under tropical conditions of India. Alcohols were found to be the most dominant group of volatile compounds identified in tested wines, followed by esters and acids, with lower concentrations of aldehydes, phenols and terpenes [23].…”
Section: Aroma Compounds In Winesmentioning
confidence: 99%
“…Somkuwar et al [23] evaluated aroma composition by analyzing 64 compounds in various red wines (Cinsaut, Grenache, Cabernet Franc, Petit Verdot, Cabernet Sauvignon, Nielluccio, Tempranillo, Syrah, Merlot and Caladoc) made from grapes grown under tropical conditions of India. Alcohols were found to be the most dominant group of volatile compounds identified in tested wines, followed by esters and acids, with lower concentrations of aldehydes, phenols and terpenes [23]. In our study, alcohols were also found to be the dominant group of volatile compounds, followed by esters and acids.…”
Section: Aroma Compounds In Winesmentioning
confidence: 99%